Control and Automation: Insmoaf (Integrated Smart Modern Agriculture and Fisheries) on The Greenhouse Model - Ridwan Siskandar; Sesar Husen Santosa; Wiyoto Wiyoto; Billi Rifa Kusumah; Agung Prayudha Hidayat (Jurnal Ilmu Pertanian Indonesia, 2022)
A greenhouse is an agricultural management system that has shown the efficiency of food production. This system is an effective alternative to ensure maximum production results. Agriculture with greenhouse technology can create the desired environmental/climatic conditions. The rapid development of technology and science has led to the birth of communication between devices using IoT and AI. This technology can be applied to greenhouses in agriculture and fisheries. Research on greenhouse and microcontroller-based automation systems has been carried out, and it is interesting to be developed. Researchers make a more efficient system and can increase the quality and quantity of production. The measurement data of both modes are monitored using the web. The greenhouse prototype is supported by DHT22, DS18B20, a fan to control the greenhouse cooler, RFID as the key access to the greenhouse. DHT22 & DS18B20 sensor readings in the prototype greenhouse use an AI system with the fuzzy method. IoT and AI have been successfully implemented in models of rice fields, hydroponic farming, and fisheries using automatic modes of RTC devices and sensors. The fuzzy approach method is used to find the optimum temperature and humidity values. The fuzzy approach was successfully carried out until the temperature and humidity conditions were "ideal," "high," and "very high." This condition provides information to the microcontroller to activate which fan should turn on. In manual mode, the smartphone application controls the system properly. Keywords: artificial intelegent, control and automation, fuzzy logic, greenhouse, IoT